Are You Ready to Lead Work Without Jobs? - Boudreau, John; Boudreau, John; Donner, Jonathan (MIT Sloan Management Review, 2021)
We are moving toward a new “work operating system” that will deconstruct work into tasks/projects that may be assigned not only to employees but also to machines and contingent workers in talent marketplaces. This shift has profound implications for leaders. Some will increasingly act as project managers, while top-level leaders will gain new challenges in orchestrating an increasingly fast-moving style of working characterized by continual change and a lack of hierarchy.